Maximizing tuberculosis services through private provider engagement – A case study from Pakistan - Aamna Rashid; Surbhi Sheokand; Razia Fatima; Hammad Habib; Adeel Tahir; Asim Saleem; Poshan Thapa; Petra Heitkamp (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases)
Pakistan is the fourth highest contributor to the globally estimated 3.7 million tuberculosis (TB) cases. Due to the subpar condition of public sector facilities in Pakistan, the private sector remains the preferred choice, with over 90% of people accessing it for TB care. Aligning with the World Health Organization’s (WHO) patient-centered approach, the private provider engagement program led by Mercy Corps (MC) and supported by the Global Fund has been actively engaging the private sector for over a decade in strengthening Pakistan’s TB services through innovative interventions. Their public–private mix (PPM) strategies like, involving General Practitioners (GPs), large private hospitals, pharmacies, specimen transportation and mobile outreach chest camps, take an integrated approach (Fig. 1) to ensure treatment adherence, completion, and contact screening in reaching the last mile. In this paper, we present MC’s contributions as a case study to elaborate on the crucial role of private provider engagement in improving overall TB care, increasing TB notifications, and addressing the urgent need to identify people with undiagnosed TB.